Jilbab dan Identitas Sosial: Relasi Keberagamaan dan Status Sosial Perempuan Berjilbab di Ponorogo - Janah, Unun Roudlotul; Aini, Shofwatul (FIKRAH, 2019)
The use of headscarves is not only religious identity but also functions as a statement of the value or social status of a person who has two sides, first, ascribed, second, and can be achieved. The focus of this article is to find out how the description of social identity for veiled women in Ponorogo and its consequences. The results of data analysis using symbolic interactionalism theory show some of the first findings, the pattern of life of religiosity (religiosity) of veiled women and veiled Shar' i tends to lead to religious exclusivism. While medium veiled women tend to lead to pluralist religious inclusive typologies. Second, for veiled and veiled Shar' i women, headscarves are social identities whose dimensions are shaped by "the trust" religious norms and values that must be adhered to and carried out in their community. While for medium veiled women, headscarves are social identities based on religious norms without having to deny the truth of religious teachings held by other groups in the context of social relations and community relations.